Pengaruh Sistem Antrian, Optimalisasi Layanan Teller Dan Banking Hall Terhadap Kepuasan Nasabah Dalam Perspektif Lembaga Keuangan Islam - Zahra, Nurul; Padli Nasution, Mhd. Irwan; Ilhamy Nasution, M. Lathief (Universitas Labuhanbatu, 2023)
Basically, bank employees on duty, especially tellers, have worked according to applicable procedures. However, this does not rule out the possibility that the transaction customer is satisfied with the services provided. This study aims to determine the effect of the queuing system, optimizing teller services, and banking halls on customer satisfaction at Bank Syariah Indonesia KCP Medan Imam Bonjol. This type of research used by researchers is to use quantitative research methods. The population in this study were customers of Bank Syariah Indonesia KCP Medan Imam Bonjol, totaling 587 customers, and the number of samples was 41 customers. By using the technique of taking random sampling. Data collection techniques used questionnaires and data processing using IBM SPSS 21. The results of this study indicate that the value